Análise do desempenho de blockchain no gerenciamento de transações em microgrids de energias renováveis - Silva, Thiago Valença (2020)
Since the creation of Bitcoin by Satoshi Nakamoto in 2009, adopting the network that manages its transactions, Blockchain, has been proposed, for purpose of substituting a third party of trust in many systems, for among other benefits, reducing costs that including it leads, for example a banking system in comparison with bitcoin. Although the fact that the substitution of a trust system appears to minimize taxes for the final user, it must be studied deeply for verifying if gains are really obtained from this swap. This work performs an experimental study, analyzing the behavior of an energy management network that uses blockchain for validate transaction. The experiment is executed operating a monitoring of two environment of two environments in which users request transactions inside the developed management system. The number of accounts that request in simultaneous way these transactions is changed in which environment while a script keep track of values of CPU and GPU temperature, CPU and GPU utilization and RAM memory utilization. The first mentioned environment uses NodeJS for management and validates transactions by performing usual checks such as login validation from the cache, the second environment uses NodeJS, as well as the first, for management and validates transactions from smart contracts on an Ethereum network. At the end, the study verify which system uses further resources, in the one which manages transactions with block chain in comparison with the first environment. The work conclude also that the resource most requested by the execution in blockchain is the RAM memory that shows high indexes of utilization in the second environment of simulation. Finally, it is verified that although blockchain reinforces security dispensing cost from an intermediate, it adds hardware cost its management.